Description of Particulate Matter2,5 with Library Worker's Health Complaint in Campus B Universitas Airlangga - Nola Fitria (Universitas Airlangga, 2016)
Abstract: PM2,5, and temperature are one of the physical factors that can affect indoor air quality. Indoor air quality affect human health because most people spend their time in room, that causing health complaint. The purpose of this study was to describe the PM2,5, temperature, and characteristics of worker with health complaint in Campus B of Airlangga University. The research was observational with cross sectional design, and analyzed descriptively. Data was collected by measuring of PM2,5, and temperature, observing, and interviewing. The results showed that the number of respondents who suffered health complaint were 75.00%. The most of health complaint in worker is sneezing. The cross-tabulation between PM2,5 and health complaint fulfi lled the standard were 100.00%; temperature and health complaint was not fulfi lled the standard were 100.00%. Most of workers who have health complaint is the age group of less than or equal to 40 years with female sex, and working period is less than or equal to 5 years. It is suggested to the library to set air conditioner according to KepMenKes RI No. 1405/MENKES/SK/XI2002 18-28°C, to maintain technical and non-technical AC, to do medical check up regularly for workers, to spend time out of building while not working.Keywords: PM2,5, temperature, health complaint, library